Effect of Low Seed Rate on Seed and Forage Yield of Alfalfa in the River Nile State, Sudan - A. A. Tambal, Hassan A. A. Tambal; A. M. Khair, Mohamed (Gezira Journal of Agricultural Science, 2021)
An on-farm survey of plant population of one year old, yet highly productive alfalfa ( Medicago sativa L .) swards in Khartoum North area, revealed that the plant population after one year from establishment, was equal to that resulting from a seed rate of I .5 kg/ha (i.e. 2.8% of the sown seeds). This suggested that the optimum seed rate for the production of each of the forage and seed of alfalfa in Sudan should be reconsidered. In this context, an experiment was conducted at Hudeiba Research Station for three years during the period of Dec. 1995 - January 1998 to study the time course forage and seed yield patterns of alfalfa sown with five low seed rates (i.e., 2.4, 4.8, 7.2, 9.6 and 12 kg/ha). The results indicated that the highest seed rate (12 kg/ha) produced the highest forage yield in a few cuts only. The variations among the time course forage yields of the various seed rates over the two years were either nonsignificant or enatic. The cumulative annual forage yield of the two higher seed rates, (9.6  and 12 kg/ha) was invariably higher than those of the other seed rates. For seed yield, the lowest seed rate (i.e., 2.4 kg/ha) resulted in the highest seed yield in the first two seed production cycles (SPC) in 1996 as well as in the annual total of the first year. Differences among the seed rates in other SPCs as well as the annual total of 1997 were either lacking or erratic. It is therefore, concluded that for dual purpose (forage and seed) alfalfa, the seed rate should not exceed 9.6 kg/ha, and for seed production the seed rate of 2.4 kg/ha is the optimum.